2023
DOI: 10.3390/nu15061523
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention of Elateriospermum tapos Yoghurt in Obese Dams Mitigates Intergenerational Cognitive Deficits and Thigmotactic Behaviour in Male Offspring via the Modulation of Metabolic Profile

Abstract: Maternal obesity is an intergenerational vicious cycle and one of the primary causes of cognitive deficits and high anxiety levels in offspring, which often manifest independently of sex. It is proven that curbing the intergenerational inheritance of obesity through early intervention during the gestation period has a positive outcome on the body composition, cognitive function, and anxiety level of the offspring. A recent discovery shows that the consumption of Elateriospermum tapos (E. tapos) seed extract mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Animal studies have demonstrated that excessive intake of HFD by dams during pregnancy leads to a high level of adiposity and cholesterol on PND 21 [ 37 , 38 ]. Similarly, a meta-regression study shows that female offspring of HFD fed dams shows persistent increase of triglycerides, FBG level, and insulin concentration [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that excessive intake of HFD by dams during pregnancy leads to a high level of adiposity and cholesterol on PND 21 [ 37 , 38 ]. Similarly, a meta-regression study shows that female offspring of HFD fed dams shows persistent increase of triglycerides, FBG level, and insulin concentration [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, male offspring are more likely to encounter a greater extent of adverse effects in utero compared to their female counterparts [34]. Considering the potential side effects associated with modern medicine, researchers led by Naomi et al, (2023) have developed a novel plant extract (E. tapos)-integrated yogurt that demonstrates transgenerational effects specifically targeting maternal obesity [10]. Despite its efficacy, the precise molecular mechanism underlying this effect remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgency to develop complementary and alternative medications to curb maternal obesity. In these, a currently developed Elateriospermum tapos (E. tapos) yogurt has shown promising effect in maternal obesity [10] and the improvement of body composition in male and female offspring [11]. E. tapos yogurt has been found to possess a rich concentration of antioxidants and various other bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative status was measured in serum and hypothalamus as described in a previous study by Naomi et al, 2023 [ 32 ]. To determine the hypothalamic levels of FRAP and GSH, the hypothalamus was minced and diluted with ice-cold phosphate buffer saline (0.02 M) with a pH of 7 at a ratio of 1:15 ( w / v ).…”
Section: Methodsmentioning
confidence: 99%